ANALYSIS OF THE BIOCHEMICAL ASPECTS OF HYPOVITAMINOSE D AND ITS CLINICAL REPERCUSSION - de Azevedo, João (2017)
Hypovitaminosis D is an important deficiency disease and has a range of clinical repercussions of great importance and prevalence in medical practice. The deficiency of vitamin D bioavailability is largely responsible for the various clinical manifestations of this disease. This literature review seeks to elucidate the biochemical aspects of vitamin D formation and to analyze its main repercussions on body metabolism and homeostasis.